A5.11 alarmins S100A8/S100A9 stimulate osteophyte formation in experimental osteoarthritis and predict osteophyte progression in early human osteoarthritis. (31st January 2014) - Schelbergen, R F P; de Munter, W; van den Bosch, M H J; Lafeber, F P J G; Sloetjes, A; Vogl, T; Roth, J; van den Berg, W B; van der Kraan, P M; Blom, A B; van Lent, P L E M
Abstract : Background and Objectives: The main pathological feature of osteoarthritis (OA) is degradation of the articular cartilage. However, other important hallmarks include subclinical inflammation of the synovium and ectopic formation of new bone and cartilage at the ligaments or joint margins, termed osteophytes. Selective depletion of synovial macrophages prevents development of osteophytes in collagenase induced OA. Alarmins S100A8 and S100A9 are major products of activated macrophages regulating cartilage damage and synovial activation during murine and human osteoarthritis (OA). In the current study we investigated whether S100A8 and S100A9 are involved in osteophyte formation during experimental OA and if S100A8/A9 predicts osteophyte progression in early human OA. Materials and Methods: OA was elicited in S100A9 -/- and wild-type C57Bl/6 mice in two experimental models that differ in degree of synovial activation. Osteophyte size, S100A8, S100A9 and VDIPEN expression was measured histologically. Chondrogenesis was induced in murine mesenchymal stem cells in the presence of S100A8. Levels of S100A8/A9 were determined in plasma of early symptomatic OA patients of the CHECK cohort study at baseline and development of osteophytes measured after 2 and 5 years. Results: S100A8 and S100A9 protein levels in the synovial lining and serum coincide with osteophyte development in collagenase-induced OA (CIOA), in which synovial activation is high. Osteophyte size was drastically reduced in S100A9 -/- mice on day 21 and 42 of CIOA, in the medial collateral ligaments (58% and 93% reduction) and at medial femur and tibia (62% and 67% reduction). In contrast, osteophyte size was not reduced in S100A9 -/- mice during destabilised medial meniscus OA, in which synovial activation is scant. S100A8 increased expression and activation of MMPs during micromass chondrogenesis, thereby possibly increasing cartilage matrix remodelling allowing for larger osteophytes. Interestingly, early symptomatic OA patients of the CHECK study with osteophyte progression after two and five years had significantly elevated S100A8/A9 plasma levels at baseline, while CRP, COMP and ESR were not higher. Conclusions: S100A8/A9 stimulate osteophyte formation in experimental OA with high synovial activation and may be used as a marker to predict osteophyte formation in early human OA.